Determinants of ageing in Romania: Evidence from regional-level panel analysis - Dănuţ-Vasile Jemna; Mihaela David (CES Working Papers, 2021)
At different stages, all countries of the world are going through the demographic ageing process, with the most diverse economic and social implications. Romania has entered this process since the communist period, as a result of both the demographic transition and the transformations imposed by the demographic and economic policies implemented by the state. After 1990, the transition period has accelerated the increasing pace of this phenomenon, especially through increased migration, declining fertility and changes in the labour market. The regional economic, social and demographic gaps inherited from the past were accentuated after the fall of the totalitarian regime, so that the population ageing has intensified and it is experienced differently at the territorial level. This study aims at identifying the determinants of the increase in population ageing, along with the decrease in the share of young population, across the eight development regions of Romania, during the 1995- 2018 period.
Keywords: 330; demographic transition; demographic ageing; Romania; regional level; heterogeneous panel data